2017
DOI: 10.18632/oncotarget.14682
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear PRMT5, cyclin D1 and IL-6 are associated with poor outcome in oropharyngeal squamous cell carcinoma patients and is inversely associated with p16-status

Abstract: Protein arginine methyltransferase-5 (PRMT5) plays an important role in cancer progression by repressing the expression of key tumor suppressor genes via the methylation of transcriptional factors and chromatin-associated proteins. However, very little is known about the expression and biological role of PRMT5 in head and neck cancer. In this study, we examined expression profile of PRMT5 at subcellular levels in oropharyngeal squamous cell carcinoma (OPSCC) and assessed its correlation with disease progressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 50 publications
0
24
0
Order By: Relevance
“…in relation to cancer. PRMT5 acts as cancer-inducing gene by promoting cell proliferation (4)(5)(6)(7)(8), inhibiting transcription of tumor suppressor genes (4,(9)(10)(11)(12)(13) and inducing metastatic predisposition via epithelial-mesenchymal transition (14). The symmetric dimethylation of the arginine residues of histones H3 and H4 by PRMT5 triggers the modification of the chromatin structure and alterations in the expression patterns of diverse genes (3,(15)(16)(17).…”
Section: Protein Arginine Methyltransferase 5 Is Implicated In the Agmentioning
confidence: 99%
See 1 more Smart Citation
“…in relation to cancer. PRMT5 acts as cancer-inducing gene by promoting cell proliferation (4)(5)(6)(7)(8), inhibiting transcription of tumor suppressor genes (4,(9)(10)(11)(12)(13) and inducing metastatic predisposition via epithelial-mesenchymal transition (14). The symmetric dimethylation of the arginine residues of histones H3 and H4 by PRMT5 triggers the modification of the chromatin structure and alterations in the expression patterns of diverse genes (3,(15)(16)(17).…”
Section: Protein Arginine Methyltransferase 5 Is Implicated In the Agmentioning
confidence: 99%
“…Additionally, PRMT5 induces transcriptional inhibition by directly methylating the tumor suppressor proteins p53 and E2F1, thus bestowing advantages for cancer cell survival (9,13). Recent studies have demonstrated that PRMT5 suppresses the expression of E-cadherin, the hallmark of EMT transition, through interactions with Ajuba and the E-cadherin transcription factor Snail (6,14). PRMT5 has been extensively characterized in relation to various types of cancer and its emerging role as a potential oncoprotein is of significant clinical interest.…”
Section: Protein Arginine Methyltransferase 5 Is Implicated In the Agmentioning
confidence: 99%
“…For instance, high PRMT5 expression correlated with low overall survival and had over 1.7 times higher death risk than the patient who has low PRMT5 expression [41]. Together, these studies have identified PRMT5 as a promising therapeutic target in cancers.…”
Section: Histone Methylases As Potential Therapeutic Targets In Cancermentioning
confidence: 92%
“…PRMT5 deficiency also led to apoptosis in differentiated glioblastoma cells however, in glioblastoma neurospheres it led to G 1 cell cycle arrest through increased protein expression of p27 and a decrease in phosphorylation of pRb [ 120 ]. PRMT5 expression correlated with cyclin D1 protein levels, while also inversely correlating with p16 levels [ 121 ]. Nuclear PRMT5/p16-negative tumors were associated with poor prognosis in oropharyngeal squamous cell carcinoma when compared to nuclear PRMT5-negative/p16- positive tumors [ 121 ].…”
Section: Protein Arginine Methylationmentioning
confidence: 99%
“…PRMT5 expression correlated with cyclin D1 protein levels, while also inversely correlating with p16 levels [ 121 ]. Nuclear PRMT5/p16-negative tumors were associated with poor prognosis in oropharyngeal squamous cell carcinoma when compared to nuclear PRMT5-negative/p16- positive tumors [ 121 ]. PRMT5 is found to be overexpressed in many cancer types, including glioblastoma [ 118 , 122 ], lung [ 123 ], mantle cell lymphoma [ 124 ], ovarian [ 125 ] and prostate cancer [ 126 ].…”
Section: Protein Arginine Methylationmentioning
confidence: 99%